General surgery risk reduction - Coventry, Brendon J. (Surgery: Complications, Risks and Consequences, 2014)
Written by internationally acclaimed specialists, General Surgery Risk Reduction expands on complications associated with surgery and how to reduce them, the availability of relevant information and the rapid advancements of surgical technology. Chapters provide pertinent and concise procedure descriptions creating a book that is both comprehensive and accessible. Stages of operative approaches with relevant technical considerations are outlined in an easily understandable manner. Complications are reviewed when appropriate for the organ system and problem. The text is illustrated throughout by line drawings and photographs that depict anatomic or technical principles. Forming part of the series, Surgery: Complications, Risks and Consequences, this volume General Surgery Risk Reduction provides a valuable resource for all general surgeons and residents in training. Other healthcare providers will also find this a useful resource.